Using modified atmosphere packaging for storing ‘van dyke’ mango (mangifera indica l.) fruit (2005)
‘Van Dyke’ mango fruits were harvested at physiological maturity and stored in active modified atmosphere conditions using different plastic packages (modified atmosphere packaging, MAP). Two-fruit-samples were placed in sealed caliber 2 and caliber 3 low density polyethylene packages (LDPE), using two initial atmosphere gas mixtures. Wrapped fruit and control fruit (without bagging) were kept at 12 °C and 90% relative humidity (RH) for 30 days plus 5 days’ shelf life at 18 °C and 70% RH. Caliber 3 LDPE film ensured that injected O2 concentration remained more stable and increased CO2 content during storage time than caliber 2 film. MAP treatment increased fruit shelf-life by delaying the ripening process. MAP drastically reduced fruit weight loss and increased ascorbic acid content compared to control. Negative correlation was found between fruit weight loss and fruit ascorbic acid content and O2 concentration within the plastic film and fruit ascorbic acid content. By contrast, there was direct correlation between CO2 content within MAP and the ascorbic acid content of fruit. Mango fruit wrapped in caliber 2 PE film ensured the longest extension of the ripening period, without incurring fruit skin lesions. Fruit in caliber 3-PE-film failed to ripen due to flesh softening being inhibited and organic acid degradation.